The Effect of Cash Turnover and Receivables Turnover on Return on Assets (ROA) in Manufacturing Companies in The Healthcare Sector of The Pharmaceutical Industry Listed on The IDX in 2016-2020 - Defia Riski Anggarini; Dina Rahma Safitri; Dhiona Ayu Nani (Universitas Warmadewa, 2022)
This study aims to examine the effect of cash turnover and accounts receivable turnover on Return on Assets (ROA) in manufacturing companies in the pharmaceutical industry health sector. The population in this study was 20 companies using a sampling technique, namely the purposive sampling technique. Based on the predetermined sampling criteria, a sample of 10 companies was obtained in 2016-2020. The research period was carried out for 5 years with a sample of 10 companies so that the total observations used were 50 data. The analytical method used is the panel data regression analysis method using the statistical tool Eviews 9.0. The results of the t-test showed that cash turnover had no significant effect on ROA, and accounts receivable turnover has a significant positive effect on ROA. Then, the results of the F test show that cash turnover and accounts receivable turnover together have a significant positive effect on ROA.